Strategi Komunikasi Persuasif Member Bisnis MLM Millionaire Club Indonesia(MCI) untuk Meningkatkan Penjualan di Kabupaten Karawang - Nurlela, Nurlela; Ramdhani, Muhammad; Budhiarti, Tri Widya (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
Multi-Level Marketing (MLM) is a branch of direct selling, in which sellers are expected to have persuasive communication skills to influence consumer attitudes and generate interest in the offered products. Millionaire Club Indonesia (MCI) is one model of Multi Level Marketing (MLM) business that sells and produces health and beauty products and has been established since 2010. Multi Level Marketing (MLM) members of Millionaire Club Indonesia (MCI) are spread across Indonesia, including in Karawang Regency. The objective of this research is to understand the persuasive communication strategies used by MLM members of Millionaire Club Indonesia (MCI) to enhance sales in Karawang Regency, West Java. The theory employed in this study is the AIDDA Theory proposed by Wilbur Schramm. The research findings indicate that Multi Level Marketing (MLM) members of Millionaire Club Indonesia (MCI) employ various persuasive communication strategies such as promoting on social media with appealing captions, sharing testimonials, providing direct consumer education, delivering excellent customer service, offering promotions and easy payment solutions. This aligns with the AIDDA theory, as Multi Level Marketing (MLM) members of Millionaire Club Indonesia (MCI) engage in communication to generate consumer interest (Interest). Once consumers show interest in knowing about the products offered by Millionaire Club Indonesia (MCI) members, the members must strive to cultivate desire (Desire) in the consumers' minds, as interest serves as the starting point for generating the decision (Decision) to purchase the offered products. This is followed by the consumers making the decision to take (Action). Keywords: Multi-Level Marketing (MLM), Millionaire Club Indonesia (MCI), AIDDA